Optimizing Facilities and Infrastructure Management to Support School Bussiness Units as Income Generators - Alim, Siti Fatika; Sutama, S (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study aims to analyze the infrastructure management strategy in supporting the development of school business units as an alternative funding source at Aisyiyah Gemolong Elementary School. The background of this study is based on the increasing operational needs of community-based private schools and the importance of funding innovation through the productive utilization of school assets. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation. The results show that Aisyiyah Gemolong Elementary School has successfully developed six business units based on school assets, namely the hall as a meeting hall, the school kitchen as Fatimah Catering, the Ayam Geprek Sako food stall, the Khadijah Shop, Aisya Tour and Travel, and the Aisar psychology bureau. These business units are managed by the Vice Principal for Personnel by implementing systematic management functions, starting from planning, organizing, implementing, to monitoring. This approach has a direct impact on increasing school revenue by an average of Rp200,000,000 per month which is used to support teacher welfare, school operations, and social programs such as free Umrah. This study concludes that optimizing facilities and infrastructure through a school entrepreneurship model can be an effective strategy in creating financial independence for educational institutions.